Enhancing Food Security Through Green Canteen Initiatives: A Case Study of the Role of Elementary Schools in Sustainable Nutrition Education (Jurnal Bina Praja, 2025)
The problem of child nutrition in Southeast Asia, including Indonesia, remains a serious issue due to the triple burden of malnutrition. Although Indonesia has made progress in reducing malnutrition rates, challenges persist in addressing stunting, undernutrition, and childhood obesity. Socioeconomic factors and unhealthy dietary patterns further exacerbate these conditions. Sustainable nutrition education in schools, implemented through green canteen initiatives, serves as a strategy to introduce healthy eating habits from an early age. This initiative aligns with the Sustainable Development Goals (SDGs) and the national program Asta Cita, where sustainable nutrition education contributes to strengthening children’s food security. This study aims to explore initiatives for implementing green canteens in primary schools as a means of providing healthy food and promoting sustainable nutrition education to enhance students’ food security. A qualitative approach was employed with data obtained through interviews, observations, and documentation, and analyzed through reduction, display, and conclusion drawing. The results indicate that green canteens contribute to enhancing students’ food security by fostering healthy eating habits and improving nutrition literacy. Furthermore, the success of the program depends greatly on the involvement of schools, teachers, students, and parents. These findings reinforce the strategic role of elementary schools as key agents in promoting food security and sustainable nutrition education at the local level.
Keywords: Green Canteen; Food Security; Sustainable Nutrition Education; Sustainable Development Goals; Asta Cita